The effect of interpersonal communication skills and work motivation on performance of marketing employee - Herdiana Abdurrahman, Nana (International Journal of Engineering and Technology, 2018)
To improve and maintain the performance of the marketing department employee, the company should improve the capacity and capability of the employees. This research aimed to investigate the influence of interpersonal communication and work motivation on employee performance marketing. This research uses a quantitative approach method with path analysis method. This study uses survey technique with the primary data collection tool in the form of a questionnaire. The study was conducted at the Jabar Banten Shariah Bank Bandung branch, with respondents as many as 33 people. The test results show that partial and or simultaneously, interpersonal communication and work motivation have significant positive effect on employee performance. The results show that the value of the determinant obtained for 0808, this means that the variables of interpersonal communication and motivation can explain the employeesâ€™ performance by 80.0 %, while 19.2 % is influenced by other variables that are not included in the model. Epsilon factors are leadership, organizational culture, facilities and infrastructure in the works, and others. The result show that performance of the marketing department can be improved through the development of interpersonal communication capacity of employees and strengthening of motivation to work. Â Â